2012
DOI: 10.1016/j.jinsphys.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of salivary glands in ixodid ticks

Abstract: Studies of tick salivary glands (SGs) and their components have produced a number of interesting discoveries over the last four decades. However, the precise neural and physiological mechanisms controlling SG secretion remain enigmatic. Major studies of SG control have identified and characterized many pharmacological and biological compounds that activate salivary secretion, including dopamine (DA), octopamine, γ-aminobutyric acid (GABA), ergot alkaloids, pilocarpine (PC), and their pharmacological relatives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…In particular, two neuropeptides, myoinhibitory peptide (MIP) and SIFamide, have been found to be co-expressed in the pair of giant neurons in the synganglion whose axonal projections reach the basal regions of type II and III acini (Šimo et al, 2009a,b, 2011, 2012, 2013, 2014a). The SIFamide receptor, as evidenced by immunostaining, was found in proximity to the acinar valve (basal region of acini), suggesting its role in control of this structure (Šimo et al, 2009b, 2013).…”
Section: Tick Salivary Glandsmentioning
confidence: 99%
“…In particular, two neuropeptides, myoinhibitory peptide (MIP) and SIFamide, have been found to be co-expressed in the pair of giant neurons in the synganglion whose axonal projections reach the basal regions of type II and III acini (Šimo et al, 2009a,b, 2011, 2012, 2013, 2014a). The SIFamide receptor, as evidenced by immunostaining, was found in proximity to the acinar valve (basal region of acini), suggesting its role in control of this structure (Šimo et al, 2009b, 2013).…”
Section: Tick Salivary Glandsmentioning
confidence: 99%
“…Aminergic and peptidergic neuronal cells were characterized by immunohistochemistry (IHC) (Hummel et al, 2007; Šimo et al, 2009a; 2009b; 2011b). Our previous study utilized 15 different antibodies, which were originally raised against neuropeptides in many different species of insects and crustaceans, and found that the synganglion was rich in neuropeptides (Šimo et al, 2009a); these findings were confirmed by a peptidomic analysis (Neupert et al, 2009), as well as an analysis of homology-based neuropeptide gene prediction (Christie, 2008; Šimo and Park, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…One provocative possibility is that one or more of Hk1's PBPs bind neurotransmitters, which are derived from amino acids and would be released by the host in response to tissue injury (i.e., formation of the feeding lesion) (Askenase et al, 1995; Dai et al, 2010; Theoharides et al, 2012). Tick saliva also contains a plethora of bioactive molecules, including dopamine and dopamine sulfate (Koci et al, 2014; Simo et al, 2012; Simo et al, 2011; Yalcin et al, 2010). Interestingly, using qRT-PCR, we recently reported significantly greater induction of c-di-GMP-dependent genes by B. burgdorferi in feeding nymphs compared to larvae (Caimano et al, 2015).…”
Section: Discussionmentioning
confidence: 99%